Professional nursing identity: a perspective through the brazilian printed media lenses - Amina Regina Silva; Maria Itayra Padilha; Vânia Marli Schubert Backes; Juliana Bonetti de Carvalho (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To analyze the historical events of the nursing profession presented by the Brazilian print media and that were configured as important in the (re/des) construction of the professional identity, from 1980 to 1986. Method: Qualitative research with a documental historical nature guided by historical investigation process, using 80 articles published in newspapers of great national circulation. Results: They portrayed the nursing struggles and representative entities to improve working conditions, the highlights for intercurrences in the nursing area, as well as the media portrayal of the stereotype of nursing at the time. Conclusion: The stereotypes traced by print media result in a double impact on nursing and its professional identity. On the one hand, it adds visibility to the struggles and gains of the category, and on the other, it generates devaluation by portraits of intercurrences in the exercise of the profession without pertinent contextualization and explanation of the facts that approached and resulted in such an event.